Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Certainly! Let's tackle this problem step-by-step.
Given:
- 3rd term ([tex]\(a_3\)[/tex]) = 40
- 13th term ([tex]\(a_{13}\)[/tex]) = 0
In an arithmetic progression (A.P.), the nth term can be expressed as:
[tex]\[a_n = a + (n - 1)d\][/tex]
where:
- [tex]\(a\)[/tex] is the first term,
- [tex]\(d\)[/tex] is the common difference.
From the given information, we can set up the following equations:
1. For the 3rd term:
[tex]\[a + 2d = 40\][/tex]
2. For the 13th term:
[tex]\[a + 12d = 0\][/tex]
To find the common difference ([tex]\(d\)[/tex]), we can subtract the first equation from the second equation:
[tex]\[ (a + 12d) - (a + 2d) = 0 - 40 \][/tex]
This simplifies to:
[tex]\[ 10d = -40 \][/tex]
Solving for [tex]\(d\)[/tex]:
[tex]\[ d = \frac{-40}{10} = -4 \][/tex]
Now, we substitute [tex]\(d = -4\)[/tex] back into the first equation to find the first term ([tex]\(a\)[/tex]):
[tex]\[ a + 2(-4) = 40 \][/tex]
[tex]\[ a - 8 = 40 \][/tex]
[tex]\[ a = 48 \][/tex]
With [tex]\(a = 48\)[/tex] and [tex]\(d = -4\)[/tex], we want to find which term of the A.P. is 28. Let this term be the [tex]\(n\)[/tex]-th term.
Using the nth term formula again:
[tex]\[ a_n = a + (n - 1)d \][/tex]
and substituting [tex]\(a_n = 28\)[/tex]:
[tex]\[ 28 = 48 + (n - 1)(-4) \][/tex]
Simplifying the equation:
[tex]\[ 28 = 48 - 4n + 4 \][/tex]
[tex]\[ 28 = 52 - 4n \][/tex]
Rearranging to solve for [tex]\(n\)[/tex]:
[tex]\[ 28 - 52 = -4n \][/tex]
[tex]\[ -24 = -4n \][/tex]
[tex]\[ n = \frac{-24}{-4} = 6 \][/tex]
So, the term of the arithmetic progression that equals 28 is the 6th term.
Final answer:
The 6th term of the arithmetic progression is 28.
Given:
- 3rd term ([tex]\(a_3\)[/tex]) = 40
- 13th term ([tex]\(a_{13}\)[/tex]) = 0
In an arithmetic progression (A.P.), the nth term can be expressed as:
[tex]\[a_n = a + (n - 1)d\][/tex]
where:
- [tex]\(a\)[/tex] is the first term,
- [tex]\(d\)[/tex] is the common difference.
From the given information, we can set up the following equations:
1. For the 3rd term:
[tex]\[a + 2d = 40\][/tex]
2. For the 13th term:
[tex]\[a + 12d = 0\][/tex]
To find the common difference ([tex]\(d\)[/tex]), we can subtract the first equation from the second equation:
[tex]\[ (a + 12d) - (a + 2d) = 0 - 40 \][/tex]
This simplifies to:
[tex]\[ 10d = -40 \][/tex]
Solving for [tex]\(d\)[/tex]:
[tex]\[ d = \frac{-40}{10} = -4 \][/tex]
Now, we substitute [tex]\(d = -4\)[/tex] back into the first equation to find the first term ([tex]\(a\)[/tex]):
[tex]\[ a + 2(-4) = 40 \][/tex]
[tex]\[ a - 8 = 40 \][/tex]
[tex]\[ a = 48 \][/tex]
With [tex]\(a = 48\)[/tex] and [tex]\(d = -4\)[/tex], we want to find which term of the A.P. is 28. Let this term be the [tex]\(n\)[/tex]-th term.
Using the nth term formula again:
[tex]\[ a_n = a + (n - 1)d \][/tex]
and substituting [tex]\(a_n = 28\)[/tex]:
[tex]\[ 28 = 48 + (n - 1)(-4) \][/tex]
Simplifying the equation:
[tex]\[ 28 = 48 - 4n + 4 \][/tex]
[tex]\[ 28 = 52 - 4n \][/tex]
Rearranging to solve for [tex]\(n\)[/tex]:
[tex]\[ 28 - 52 = -4n \][/tex]
[tex]\[ -24 = -4n \][/tex]
[tex]\[ n = \frac{-24}{-4} = 6 \][/tex]
So, the term of the arithmetic progression that equals 28 is the 6th term.
Final answer:
The 6th term of the arithmetic progression is 28.
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.